Emerging Security Considerations for NATO's Northern Flank - DELeon,P (1984)
Since the inception of the North Atlantic Treaty Organization, the northern flank nations have played quite conspicuous roles in East-West politics, although in very different ways. Norway and Denmark are charter members of NATO, Iceland joining shortly thereafter; all have been consistently supportive of NATO, albeit exercising low military profiles (e.g., neither Norway nor Denmark permits the peacetime location of nuclear weapons on their soil). Finland has traditionally acted as a buffer and broker between the Soviet Union and the other Scandinavian states, while Sweden has deliberately pursued a policy of strictly observed and well-armed neutrality. Although there have been some deviations from these general patterns, on the whole, they have held relatively constant in the post war years and need not be recounted at length here. The consensus regarding the Northern Flank is that it represents a stable geographic area, the quiet corner of Europe, one relatively devoid of the East-West volatilities and tensions which have characterized other parts of the continent over the past thirty years.